“I Have a New Understanding”: Critical Narrative Inquiry as Transformation in the English-History Classroom - Gina DeBlase (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
This case study highlights what roles classroom discussion and activity around literature, history, and society play in developing one student’s understanding of complex social issues, and what ways of talking and thinking develop over time.